Farmers persuasion regarding implementing of the methodological support for determining the performance in agricultural exploitations - Iuliana Dobre (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
This paper is a quantitative and qualitative approach of performance from Romanian agriculture exploitations, focusing on the need to implement the methods to determining of it. Are references to the content of performance, to the variables that influence, to the assimilation of methodology for assessing of the its level by managers or producers. For this purpose, are created theoretical and methodological conditions which to provide information necessary for the understanding and acceptance of application of methods for determining the performance. For this, are used the statistics in this area by presenting some methods with large utilization in production activities and in marketing and illustration, by elaborate a questionnaire from producers, to convince them to implement methods and techniques as scientific base of decisions. Considering the multitude of factors which acting on achieving performance, the results show, undoubtedly, the need of minimum of economic and managerial knowledge which to put in value the potentialities of exploitations.
Keywords: 330; performance; agricultural exploitations; methodological suport; persuasion; farmers